Questions & answers. Animals - "Miles Kelly" (Miles Kelly Essex, 2016)
Questions and Answers Animals is a large format paperback question-and-answer book, ideal for younger readers who are mad about animals. Children will love finding out the answers to interesting aspects of animal life in a fun and concise way. Covering three core subject areas of Big Cats, Monkeys and Apes and Baby Animals, there is lots of choice for even the pickiest of readers. The fun questions are clearly answered and dramatic illustrations and photos help explain things further. Cartoons help to keep kids hooked and extra-special facts entertain. Activity panels throughout provide tips on further learning